2020
DOI: 10.1186/s12979-020-00184-y
|View full text |Cite
|
Sign up to set email alerts
|

Moderate- to high intensity aerobic and resistance exercise reduces peripheral blood regulatory cell populations in older adults with rheumatoid arthritis

Abstract: Objective Exercise can improve immune health and is beneficial for physical function in patients with rheumatoid arthritis (RA), but the immunological mechanisms are largely unknown. We evaluated the effect of moderate- to high intensity exercise with person-centred guidance on cells of the immune system, with focus on regulatory cell populations, in older adults with RA. Methods Older adults (≥65 years) with RA were randomized to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 27 publications
(55 reference statements)
0
35
1
Order By: Relevance
“…Aerobic exercise interventions included bicycle riding, running on a treadmill, jogging, and walking. The control group underwent a range of usual care in 7 studies [ 33 , 34 , 36 , 38 , 39 , 41 , 44 ], motion exercises in 1 study [ 35 ], education programs in 3 studies [ 37 , 40 , 45 ] and home-based nonaerobic exercises in 2 studies [ 42 , 43 ]. (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerobic exercise interventions included bicycle riding, running on a treadmill, jogging, and walking. The control group underwent a range of usual care in 7 studies [ 33 , 34 , 36 , 38 , 39 , 41 , 44 ], motion exercises in 1 study [ 35 ], education programs in 3 studies [ 37 , 40 , 45 ] and home-based nonaerobic exercises in 2 studies [ 42 , 43 ]. (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen articles were excluded: 8 articles' intervention was not aerobic exercise; 7 articles' outcome indicators did not meet the inclusion criteria; 2 articles' study type did not match; and 2 articles had incomplete data results. Thirteen RCTs were finally included [33][34][35][36][37][38][39][40][41][42][43][44][45], studying a total of 967 RA patients. The study flow diagram for the systematic search process is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention studies also show inconsistent effects of exercise training on T REG cells, which may be explained by differences in phenotyping approach, exercise prescription, or patient population. For example, CD4 + CD25 + CD127 − FoxP3 + T REG cells have been shown to decrease following 20 weeks of exercise training in individuals with rheumatoid arthritis ( 204 ). In contrast, T REG cells identified via CD25 + expression on CD4 + T cells increased following 12 weeks of tai chi training ( 205 ).…”
Section: Part 3: Evaluating the Effects Of Physical Activity On T-cel...mentioning
confidence: 99%
“…In terms of assessing the effects of exercise on immune parameters, the results are mixed and disappointing given the large potential to shift biomarkers in the beneficial direction (table 1). [26][27][28][29] Contributing factors include weak study designs and lack of control for numerous potential confounding factors. For example, the study by Bartlett et al 27 with 12 physically inactive adults with rheumatoid arthritis (stable, no recent medication changes) showed that 10 weeks of high-intensity interval walking training reduced disease activity and improved several measures of innate immune function.…”
Section: Exercise and Infectious Diseasementioning
confidence: 99%